Mesearch, Research, and Qualitative Reasoning - Christopher S. Collins (International Journal of Qualitative Methods)
In all research and all methods, reflexivity and the researcher’s awareness of the environment being studied are both valuable and profound. Qualitative research incorporates a standard of reflexivity, recognizing that the researcher is an instrument who cannot be hidden, ignored, or treated as a disembodied third person. This article serves as a specific invitation to reflexivity. The aim is to cultivate a healthier approach to knowledge production through heightened self-awareness, consciousness, and reflexivity—mesearch.